Process Systems Engineering Tools for the Design of Ionic Liquids and Integrated Biorefineries - Chemmangattuvalappil, Nishanth G.; Ng, Denny K. S. (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint contains a collection of research articles covering the recent advances of process systems engineering tools in the areas of integrated biorefineries and ionic liquid design. The reprint comprises original research contributions and review articles on these topics.